2019
DOI: 10.1038/s41598-019-44369-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome of pre-adolescent children of two ethnicities residing in three distant cities

Abstract: Recent studies have realized the link between gut microbiota and human health and diseases. The question of diet, environment or gene is the determining factor for dominant microbiota and microbiota profile has not been fully resolved, for these comparative studies have been performed on populations of different ethnicities and in short-term intervention studies. Here, the Southern Chinese populations are compared, specifically the children of Guangzhou City (China), Penang City (west coast Malaysia) and Kelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Several clinical studies on gut microbiota in intractable epilepsy reported inconsistent results, as summarized in Table 1. We presumed that the lack of consensus could be the result of inconsistency in their control over the confounding factors, such as age [23,24], body mass index [25], type of diet [26][27][28][29][30], modes of delivery [31,32], or recent antibiotic exposure [33], which are known to have an influence over the gut microbiota. Antibiotic exposure was the only variable that was consistently controlled throughout most of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies on gut microbiota in intractable epilepsy reported inconsistent results, as summarized in Table 1. We presumed that the lack of consensus could be the result of inconsistency in their control over the confounding factors, such as age [23,24], body mass index [25], type of diet [26][27][28][29][30], modes of delivery [31,32], or recent antibiotic exposure [33], which are known to have an influence over the gut microbiota. Antibiotic exposure was the only variable that was consistently controlled throughout most of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Chong and colleagues 10 identified that ethnicity played a major role in influencing the GM of pre-adolescents from two ethnic groups in a closely located rural setting in Malaysia. In contrast, Khine and colleagues 11 proposed that diet exerted a stronger influence on the GM than ethnicity alone in a comparison across Chinese children from Malaysia and southern China. To date, the effects of ethnicity on the GM of adult Malaysians have not been examined.…”
Section: Introductionmentioning
confidence: 89%
“…This sets Malaysia as a valuable setting to investigate the impact of ethnicity across communities. Previously, studies on the effect of ethnicity on the GM of Malaysians have resulted in differing outcomes 10 , 11 . Chong and colleagues 10 identified that ethnicity played a major role in influencing the GM of pre-adolescents from two ethnic groups in a closely located rural setting in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The mature human gastrointestinal (GI) microbiome type has been categorized into two operational types, determined largely by diet, geographic location, and lifestyle: the Bacteroides-Bifidobacterium type and Prevotella type. [5][6][7][8][9] The former type is predominant among Europeans, North Americans, and Eastern Asians, 5,[9][10][11] whereas the latter is common among Southeast Asians, Mongolians, and Africans. 5,10,12 Mothers transfer their microbiomes to their children during pregnancy and delivery.…”
Section: Introductionmentioning
confidence: 99%